'Durham Cathedral can be whatever you want it to be': Examining the negotiation of space and time. (December 2019) - Calvert, Arran J.
Public spaces are also spaces of contestation, in which people vie for the space they need for the purposes they need them for, and Durham Cathedral is no different. Not only do cathedrals in the 21st century need to be places of worship, they must also be tourist attractions and support community events both religious and non religious. Beginning from a much used phrase that 'Durham Cathedral can be whatever you want it to be', and building on Bergson's concept of duration, Munn's use of space-time, and Eliade's notion of sacred time, this article examines two ethnographic examples of the tensions of time and space that arise everyday in Durham Cathedral and how, through the actions of the community, spaces become places of enacted negotiation in which both space and time are malleable assemblages used to create manifold space-times.